Production Of Sodium Lignosulphonate From Isolated Lignin Of Empty Fruit Bunch : Indentification And Performance Test As A Dispersant Agent - . Ismiyati; Ani Suryani; Djumali Mangunwidjaya; . Machfud; Erliza Hambali (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Sodium lignosulphonate is a product of isolated lignin sulphonation process using NaHSO3 as sulphonation agent. This research was proposed to produce sodium lignosulphonate , to identify and to charactirize the product as dispersant agent. The lignin sulphonation process was conducted by ratio of reactant variable (NaHSO3 and lignin) 60.32%, pH 6.03 and temperature at 90.28 OC on batch reactor. The identification was carried out by Fourier Transform Infrared (FTIR) and by Liquid Chromatography Mass Spectrophotometer (LCMS). Identification using FTIR and LCMS spectrophotometer indicated that SLS produced from this study has similar characteristic with SLS standard from Aldrich (SLS-Aldrich). Performance test of SLS as dispersant materials for gypsum paste pointed out that this SLS has lower performance than SLS-Aldrich. This was caused by the purity of SLS standard, 96%. Nevertheless SLS still fulfilled the characteristic as dispersant materials for gypsum paste because it has purity of more than 80%. Keywords: lignin, sulphonation, sodium lignosulphonate, dispersant